Eucaristia e Reino de Deus - Feller, Vitor Galdino (Revista Encontros Teológicos, 2016)
O autor propõe que a concepção da Eucaristia como sinal do Reino de Deus poderia ser um critério mais objetivo para o julgamento sobre o acesso dos fiéis à mesa da comunhão. Partindo da dimensão eucarística dos Fóruns Sociais Mundiais, trabalha a dimensão escatológica da Eucaristia em suas relações com o sonho de outro mundo possível. Mostra, em seguida, sinais dessa dimensão escatológica da Eucaristia na opção pelos pobres, no cuidado com o mundo, na vivência do agradecimento. Após refletir sobre a Eucaristia como sinal e instrumento do Reino de Deus, arremata com a proposição de que se resgate a centralidade do Reino na celebração das liturgias eucarísticas. Na conclusão, pondera que todas as pessoas que lutam pelo Reino de Deus são, de certa forma, pessoas eucarísticas. Abstract:The author unfolds a new concept of the Eucharist considering it as a sign of the Kingdom of God because it could be a more objective criterion for the permission to be granted to the faithful to have access to Holy Communion. Beginning with the Eucharistic dimension of the world-wide Social Conventions he widens the scope by assuming an eschatological perspective so as to arrive at the understanding of the Eucharist and its many links with the dream of another possible world. Moreover, new insights are provided in connection with the eschatological dimension of the Eucharist which appears in one’s care for the poor, in the protection of the natural environment, and in the enjoyment of life in a spirit of thanksgiving to God. He deals further with the Eucharist as a sign and instrument of the Kingdom of God stressing the need of setting forth the idea about the Kingdom of God to be portrayed as the center in the liturgical celebration of the Eucharist. He concludes with the thought that everyone engaged in consolidating and expanding the Kingdom of God is inspired by the Eucharist.